Experience of MOOC designing and implementation in teaching philology students - Olga M. Osiyanova; Anna V. Osiyanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to one of the most important problems for the modern education, connected with educational process modernization, based on progressive information technologies. The authors focus their attention on theoretical and practical aspects of Massive Open Online Course (MOOC) designing and implementation as an educational resource and independent educational system element. Its tasks are to build an individual educational route and students supplementary professional training, to form students skills for self-organization and self-education. The paper summarizes the experience of MOOC designing and implementation in Orenburg State University philology-students educational process, which demanded pointing out the MOOC peculiar characteristics, designing algorithm for its construction and approval, evaluation of received results and defining perspectives for improving. The system analysis of MOOC peculiar characteristics and potential for educational process at university held with the use of theoretical and practical researching methods let clarify its advantages and disadvantages. Interactivity, quick evaluation of tasks, unlimited time, logical and well-structured material and the ability to perform self-control of learning results are considered to be the advantages. The dependence on the technical abilities, absence of total control of tasks accomplishment and actual teacher-student visual contact, self-sufficient learning decrease MOOCs effectivity. Stage-by-stage algorithm of MOOC design and implementation in educational process of higher education and approved in the designer MOOC Methods of teaching English for philology-students at Orenburg State University is presented. The algorithm consists of 5 consequential stages (preparative, stages of design and production, approbation, improvement and copying). Each stage has its aim and goals, content and ways for realization. Effectivity of algorithm has been proved by the 2 year experimental work. It was proved that the use of designer MOOC resources helped arrange educational process and manage educational time more sufficiently.